1992
DOI: 10.1111/j.1755-3768.1992.tb04898.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of trace elements in senile cataract

Abstract: The contents of copper, zinc and protein were determined in cortex and nucleus sections of cortical and nuclear cataracts. The results show that copper and zinc content increased in both types of cataracts, although more in the cortex than nucleus sections of the cataractous lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 9 publications
0
31
0
3
Order By: Relevance
“…On the contrary, Zn levels in senile cataractous lenses were found to be elevated in some studies [28,29]. It was suggested that the increased Zn levels may be harmful for the lens deteriorating the permeability of the membrane by oxidation of sulfhydryls or by causing a rise in the metallothionein level [29]. It was showed that the levels of Zn in diabetic senile cataracts were significantly increased when compared to the senile cataracts [18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the contrary, Zn levels in senile cataractous lenses were found to be elevated in some studies [28,29]. It was suggested that the increased Zn levels may be harmful for the lens deteriorating the permeability of the membrane by oxidation of sulfhydryls or by causing a rise in the metallothionein level [29]. It was showed that the levels of Zn in diabetic senile cataracts were significantly increased when compared to the senile cataracts [18].…”
Section: Discussionmentioning
confidence: 93%
“…In an animal study, those rats that were fed a low-Zn diet developed cataractogenesis [27]. On the contrary, Zn levels in senile cataractous lenses were found to be elevated in some studies [28,29]. It was suggested that the increased Zn levels may be harmful for the lens deteriorating the permeability of the membrane by oxidation of sulfhydryls or by causing a rise in the metallothionein level [29].…”
Section: Discussionmentioning
confidence: 95%
“…27,[35][36][37] Zinc is one of the most abundant metal ions known to play significant catalytic and structural roles in many proteins. 38 We reported that of the many divalent metal ions zinc ions produce the most significant changes in conformation and chaperone function of a-crystallin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that lens α-crystallins bind Cu(II) and prevent the formation of Cu(II)-mediated reactive oxygen species [7173]. Mini-αA chaperone indeed functions like an antioxidant by preventing Cu(II)-mediated oxidation of ascorbic acid [74].…”
Section: Antioxidant Action Of Mini-αa-chaperonementioning
confidence: 99%